Challenges of re-engineering through RPA and AI of Accounting and Audit Process – Indian Perspective. - Prasad, Dr Gutti R K; John, Dr Byju (The journal of contemporary issues in business and government, 2022)
Over the last few decades, information technology has expanded rapidly, and accounting and auditing have become increasingly vital due to the opportunities discovered. Artificial intelligence (AI) and robotic process automation (RPA) are believed that automation of decision-making systems and systems that require human intervention would become increasingly vital for dealing with change. Because technology develops quickly, integrating AI into accounting and auditing systems is a high-risk proposition. However, there aren't enough theoretical frameworks to fully explain how RPA and AI can be used to re-engineer the accounting and auditing processes. This study encapsulates the evolving RPA and AI ecosystem to address this research gap. It identifies critical challenges that must be overcome to successfully implement such auditing and accounting systems from the Indian perspective.